Pengaruh Fernand Braudel terhadap Kajian Sejarah Maritim di Indonesia - Rohman, Muhammad Habibur (IJTIMAIYA: Journal of Social Science and Teaching, 2021)
Fernand Braudel is one of the most influential historians in modern historiography. Braudel's works are considered to provide a new perspective for writing in modern historiography. As his work entitled The Mediterranean and the Mediterranean World in the Age of Philip II is considered a revolutionary study that is different from the conventional / traditional historiography tradition. This study aims to examine the role and influence of Fernand Braudel's thoughts in writing modern history. The method used is a literature review with a unit of analysis of his figures and works, that is Fernand Braudel and his work The Mediterranean and the Medoterranean World in the Age of Philip II. The research results show that Braudel's work introduces something new, namely "Total History" on the study of historical writing using a multi-dimensional approach - by including economic, social, and etc. The purpose of applying this multi-dimensional approach is so that history can be fully understood from various aspects. Other than that, it is an alternative-critic's attempt to dominate politics in the historical dimension, namely history which only emphasizes major events and focuses on big figures who tend to be political. Braudel's style of writing history (Braudelian) already given a major influence on historians who have been involved in the study of Regional History, such as Anthony Reid, M. C. Riclekfs, A.B. Lapian, I Gde Parimartha, Gusti Asnan, Singgih Tri Sulistiyono.Fernand Braudel salah satu sejarawan yang mempunyai pengaruh dalam historiografi modern. Karya-karya Braudel dianggap memberikan perspektif penulisan baru dalam historiografi modern. Sebagaimana karyanya berjudul The Mediterranean and the Mediterranean World in the Age of Philip II dianggap sebagai kajian revolusiner yang berbeda dengan tradisi historiografi konvensional/tradisional. Penelitian ini bertujuan untuk mengupas peran dan pengaruh pemikiran Fernand Braudel dalam penulisan sejarah modern. Metode yang digunakan adalah literature review dengan satuan kajian (unit of analysis) tokoh dan karyanya, yakni Fernand Braudel dan karyanya The Mediterranean and the Medoterranean World in the Age of Philip II. Hasil penelitian menunjukan bahwa karya Braudel memperkenalkan sesuatu yang baru, yakni “Total History” atas kajian penulisan sejarah dengan menggunakan pendekatan multi-dimensional – dengan memasukkan aspek-aspek ekonomi, sosial, dan sebagainya. Tujuan penerapan pendekatan multi-dimensional tersebut agar sejarah dapat dipahami secara utuh dari berbagai aspek. Selain itu sebagai upaya alternative-critic atas dominasi politik dalam dimensi sejarah, yaitu sejarah yang hanya mementingkan peristiwa besar dan terfokus pada tokoh besar yang cenderung bersifat politis. Gaya penulisan sejarah Braudel (Braudelian) telah memberikan pengaruh besar terhadap para sejarawan yang berkecimpung dikajian Sejarah Kawasan, seperti Anthony Reid, M. C. Riclekfs, A.B. Lapian, I Gde Parimartha, Gusti Asnan, Singgih Tri Sulistiyono.